2013
DOI: 10.1111/jnc.12345
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of buildup of the toxic dopamine metabolite DOPAL in Parkinson's disease

Abstract: Intra-neuronal metabolism of dopamine (DA) begins with production of 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is toxic. According to the ‘catecholaldehyde hypothesis,’ DOPAL destroys nigrostriatal DA terminals and contributes to the profound putamen DA deficiency that characterizes Parkinson’s disease (PD). We tested the feasibility of using post-mortem patterns of putamen tissue catechols to examine contributions of altered activities of the type 2 vesicular monoamine transporter (VMAT2) and aldehyde de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
175
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 54 publications
(104 reference statements)
2
175
0
1
Order By: Relevance
“…The increased DOPAC levels suggest that 1-octen-3-ol may interfere with the packaging of dopamine into synaptic vesicles, which increases autooxidation of dopamine and generation of oxidative damage and reactive dopamine metabolites such as 3,4-dihydroxyphenylacetaldehyde (36)(37)(38). Indeed, we previously found that an increase in reactive oxygen species is observed in head extracts from 1-octen-3-ol-exposed flies (16).…”
Section: Discussionmentioning
confidence: 94%
“…The increased DOPAC levels suggest that 1-octen-3-ol may interfere with the packaging of dopamine into synaptic vesicles, which increases autooxidation of dopamine and generation of oxidative damage and reactive dopamine metabolites such as 3,4-dihydroxyphenylacetaldehyde (36)(37)(38). Indeed, we previously found that an increase in reactive oxygen species is observed in head extracts from 1-octen-3-ol-exposed flies (16).…”
Section: Discussionmentioning
confidence: 94%
“…For production of 15 N-aS or 13 C, 15 N-aS, cells were grown in minimal media containing 15 N-labeled ammonium chloride or 15 Nlabeled ammonium chloride plus 13 C-labeled glucose, respectively, and the protein expression was induced with 0.8 mM isopropyl 1-thio-␤-D-galactopyranoside for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Amide resonance assignments were performed according to previously reported chemical shift assignments for intrinsically unfolded aS (20 -22). HNCA experiments of SDS-bound 13 C, 15 N-aS provided ␣-carbon chemical shifts for secondary shift analysis. For this experiment, 40 mM deuterated SDS was added to 200 M doublelabeled aS-unmodified (aS unmod ) or aS-DOPAL(1:10) monomer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VMAT2 is an H + -ATPase antiporter, which uses the vesicular electrochemical gradient to drive the packaging of cytosolic transmitter into small synaptic and dense core vesicles (8)(9)(10). VMAT2 is also essential for survival of dopamine neurons as cytosolic dopamine is neurotoxic (11,12). By sequestering intracellular dopamine into vesicles, VMAT2 prevents cytosolic dopamine accumulation and its subsequent conversion to neurotoxic species (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%